Immigration and the Evolution of Local Cultural Norms - Sophia Schmitz; Felix Weinhardt (Institute of Labor Economics (IZA), 2019)
We study the local evolution of cultural norms in West Germany in reaction to the sudden presence of East Germans who migrated to the West after reunification. These migrants grew up with very high rates of maternal employment, whereas West German families followed the traditional breadwinner-housewife model. We find that West German women increase their labor supply and that this holds within household. We provide additional evidence on stated gender norms, West-East friendships, intermarriage, and childcare infrastructure. The dynamic evolution of the local effects on labor supply is best explained by local cultural learning and endogenous childcare infrastructure.
Keywords: J16; J21; D1; 330; cultural norms; local learning; gender; immigration